1983
DOI: 10.1111/j.1432-1033.1983.tb07344.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Lys‐6 in Phospolipase A2 from Naja melanoleuca Snake Venom

Abstract: Phospholipase A2 isolated from Naja melanoleuca snake venom was modified with 4-chloro-3,5-dinitrobenzoate. The modification reaction was accelerated by the cofactor Ca2+. Micellar concentrations of the substrate analog n-tetradecylphosphocholine retarded the inactivation of the enzyme. Modification resulted in the incorporation of one mole dinitrobenzoate/mole of protein. The modified residue could be identified as Lys-6 in the amino acid sequence of the enzyme. Although the modified enzyme still retains a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition aristolochic acid is a competitive inhibitor of type I PLA 2 and showed noncompetitive inhibition in the case of type II PLA 2 from russell's viper venom [37, 38]. Type II PLA 2 venom enzyme differs from type I PLA 2 by having extended C-terminal tail [39]. This leads to differance in their pharmacological sites of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition aristolochic acid is a competitive inhibitor of type I PLA 2 and showed noncompetitive inhibition in the case of type II PLA 2 from russell's viper venom [37, 38]. Type II PLA 2 venom enzyme differs from type I PLA 2 by having extended C-terminal tail [39]. This leads to differance in their pharmacological sites of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Lys6 residues are found in PLA 2 of all Elapidae venom. It is reported that Lys6 plays an indirect role in the Ca 2+ cofactor for catalyst activity of the PLA 2 in snake venom by means of intermolecular H-bond with Ca 2+ catalytic active site residues [39]. Modification in the Lys6 might distort the binding ability of PLA 2 for substrate and cause a drastic loss in enzymatic activity [40].…”
Section: Discussionmentioning
confidence: 99%